Spectropolarimetric observations of cool DQ white dwarfs - T Vornanen; S V Berdyugina; A Berdyugin (ESO, 2022)
Following our recent discovery of a new magnetic DQ white dwarf (WD) with CH molecular features, we report the results for the rest of the DQ WDs from our survey. We use high signal-to-noise spectropolarimetric data to search for magnetic fields in a sample of 11 objects. One object in our sample, WD1235+422, shows the signs of continuum circular polarization that is similar to some peculiar DQs with unidentified molecular absorption bands, but the low S/N and spectral resolution of these data make more observations necessary to reveal the true nature of this object.